A paediatric case of lymphadenitis by toxigenic Corynebacterium ulcerans. Issue 5 (30th October 2015) - Terada, Tomomasa; Suga, Kenichi; Yamamoto, Akihiko; Ono, Akemi; Inoue, Miki; Kawahito, Masami; Mori, Kazuhiro
Abstract : Introduction: Corynebacterium ulcerans, a potentially toxigenic zoonotic agent, may produce diphtheria toxin and causes varied types of infections in humans. Cases of infection due to toxigenic C. ulcerans infection have been increasingly reported. Case presentation: A 6-year-old Japanese girl who had been vaccinated using diphtheria toxoid presented with fever and swelling in the left neck. Ultrasonography showed cervical lymphadenitis with cellulitis. C. ulcerans was isolated from the drainage specimen. The infection was cured with erythromycin administration. Her anti-diphtheria toxoid antibody level was at an adequate level for diphtheria prevention on admission and was significantly increased 3 weeks later. Zoonotic infection was considered likely, because a family cat had shown rhinitis and skin ulcers prior to symptom onset in the child. Conclusion: In addition to the number of reported cases of infection in adults, C. ulcerans infection in previously vaccinated children should also be a subject of concern in Japan.